Proses Pengungkapan Diri Seorang Gay Untuk Bisa Diterima Dalam Keluarga - Ken Meity Anggita; sri Budi Lestari (Interaksi Online, 2021)
Gay men will experience the complexity in order to do process self disclosure to his family members. Besides that, gay men have to make a choice about who and what kind of information about their sexual orientation that can be communicate and concealed from their family members. The purpose of this research is to find out about self disclosure process of gay men when they disclose their sexual orientation to their family members, and considerations that affect their decision to disclose their sexual orientation to family members. This is a qualitative research that use Social Penetration Theory and Communication Privacy Management Theory, with Phenomenology Method. Data collection method that used in this research was in-depth interview with numbers of informant 4 gay men. Results of the research showed that (1) Self disclosure process for gay men goes through quite a long stage, starting from Orientation Stage where gay men share their information on public level. Next, Exploratory Affective Stage where gay men and family members starts to talk about topics that are personal, such as sexual orientation. After that, Affective Exchange Stage where gay men start to tell the family members about their sexual orientation and receive reactions in form of acceptance to rejection. And last, Stable Exchange Stage where gay men start to feel comfortable in expressing himself to their family members. (2) In order to do self disclosure to their families, it goes through a long stage starting from being able to identify themselves, then continued with disclosure to their nearest environment and finally to their family members, that start with siblings, mother, and father. (3) Gay men have fears to disclose their sexual orientation to their parents, and it took a lot of time and courage in order to do it. (4) There are many considerations for gay to disclosre their personal information regarding of sexual orientation, such as culture, gender, contextual, motivation, and risks-benefit.